1959
DOI: 10.1021/jm50004a003
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship of Some Diamine Bis-epoxides in Mouse Leukaemia

Abstract: An extensive study of the relationship between the structure of a number of bis-epoxides and their activity against the Walker carcinosarcoma 256 in the rat has been reported by Ross.1 This study revealed a distinct correlation of the chemical reactivity of the epoxide function towards anions and the observed biological effectiveness. Diepoxybutane was found to be one of the most active compounds, while a few primary aromatic amine bisepoxides, e.g. N,N-bis(2,3-epoxypropyl)anisidine, were reported to possess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1960
1960
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…Although it has been reported [8] that TCHA can be dehydrohalogenated in methanolic solution, we have found that such solutions do not produce the desired crease recovery. \Vork of this investigation indicates that the TEPA is very sensitive to alkali and polymerizes under alkaline conditions.…”
Section: Tcha Treatmentscontrasting
confidence: 81%
See 1 more Smart Citation
“…Although it has been reported [8] that TCHA can be dehydrohalogenated in methanolic solution, we have found that such solutions do not produce the desired crease recovery. \Vork of this investigation indicates that the TEPA is very sensitive to alkali and polymerizes under alkaline conditions.…”
Section: Tcha Treatmentscontrasting
confidence: 81%
“…From the described conditions, it is not likely that the composition of matter prepared was N,N-bis(2,3epoxypropyl)amine (theoretical N = 10.97'0). Gerzon [8], in a study of the relationship between base strength and antileukemic effectiveness of some diamine diepoxides, recently reported on the reaction between ammonia and epichlorohydrin. precursor, TCHA, or the hydrochloride of the trichlorohydrin, TCHAC, to cotton has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This is an acute lymphocytic leukemia which, in our laboratory, is transplanted only in I)BA/2 mice. It has been used to detect and predict clinical activity of a number of antineoplastic compounds (13,15,(29)(30)(31)(32)(33)(34).…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Some nitrogen mustards are preferably activated in more acidic tissues [97][98]1881. Similarly, the antileukemic activity of basic epoxides is increased in more acidic environments, while an increase in the basicity of such compounds significantly increases their effectiveness and the therapeutic-toxic ratio [157]. The basicity of ellipticine, NSC 7195, is essential for its fixation to DNA, a phenomenon which is favored at the more acidic intracellular pHs [IS6].…”
Section: Implications In Cancer Research and Treatment Questions And mentioning
confidence: 99%